Konstrukcje tożsamości i bogactwo kulturowe w autobiografiach Güntera Grassa i Marcela Reicha-Ranickiego jako wyzwanie translatorskie - Mysakowska, Monika (My University, 2012)
Celem niniejszej rozprawy doktorskiej jest analiza polskich przekładów dwóch współczesnych autobiografii niemieckich: Mein Leben Marcela Reicha-Ranickiego i Beim Häuten der Zwiebel Güntera Grassa pod kątem konstrukcji tożsamości autorów i bogactwa kulturowego tekstu. Punktem wyjścia do przeprowadzenia właściwej krytyki tych dwóch przekładów było wyznaczenie zadań krytyki przekładu autobiografii w oparciu o naukowe opracowania z zakresu teorii przekładu artystycznego, teorii krytyki przekładu, literaturoznawstwa, a także innych dyscyplin naukowych, takich jak komparatystyka, kulturoznawstwo, filozofia, historia czy etnologia. To interdyscyplinarne spojrzenie na krytykę przekładu wymuszone zostało jej kompleksowym charakterem i złożonością problemu badawczego. Takiego spojrzenia wymagała także autobiografia jako gatunek literacki wymykający się jednoznacznej typologii. W pracy wyłoniony został model krytyki przekładu autobiografii, który umożliwił przeprowadzenie analizy przekładów omawianych dzieł. Model opiera się zasadniczo na teoretycznych rozważaniach Paula Ricœura i jego postulatach dotyczących istoty i funkcji przekładu artystycznego. Został on tak skonstruowany, aby umożliwić potraktowane każdej autobiografii jako przypadku indywidualnego, a nie elementu podlegającego ogólnym procedurom translatorskim i procedurom krytyki przekładu.

The aim of the present work is the analysis of Polish translations of two contemporary German autobiographies: Mein Leben by Marcel Reich-Ranicki and Beim Häuten der Zwiebel by Günter Grass, with the focus on the construction of authors’ identities and cultural wealth of texts. The starting point for a correct critique of translation of both autobiographies was to set the tasks of the autobiography translation’s critique based on scientific works on the theory of literary translation, theory of translation critique, literary studies, and also other disciplines such as comparative studies, cultural studies, philosophy, history and ethnology. This interdisciplinary perspective on the critique of translation was forced by its global character and the complexity of the research matter. Additionally, autobiography as a literary genre that seems difficult to place unequivocally within the confines of any literary typology requires such a perspective. The theoretical part of the thesis was devoted to theory of autobiography with the aim of selecting its relevant genre characteristics that regulate translating works about factual narration. Critique of literary translation also required a theoretical foundation. A model of the critique of autobiography’s translation emerged in the thesis, and it enabled the analysis of the aforementioned works. The model is based substantially on Paul Ricœur’s theoretical ruminations as well as his postulates regarding the essence and functions of literary translation. The model was construed in such a way that it enabled an individualized approach to any autobiography, hence it made it possible not to treat autobiography as an element that is subject to general procedures of translation and of critique of translation.

Diese Dissertation wendet sich der übersetzungskritischen Analyse von zwei polnischen Übertragungen der Autobiographien von Günter Grass und Marcel Reich-Ranicki zu. Die Analyse konzentriert sich auf einen komparatistischen Vergleich des Originals mit der Übersetzung unter Berücksichtigung der theoretischen Grundlagen und anhand des in der Arbeit entworfenen Modells. Dieses Modell der Übersetzungskritik der Autobiographie, das durch die philosophisch untermauerten übersetzungskritischen Reflexionen von Paul Ricœur wesentlich inspiriert wurde, ist so konstruiert, dass es auf die Einzigartigkeit einer Autobiographie aufmerksam macht. Die in dem Modell vorgesehenen Kategorien gehen auf die jeweilige autobiographische Narration und das gattungsspezifische Profil der Autobiographie zurück. Diese Sichtweise impliziert, dass Autobiographien als Kunstwerke angesehen werden, deren Wiedergabe unter Berücksichtigung der anvisierten Sinnkonstruktion des Autors und seiner Weltanschauung vollzogen werden muss. In der Dissertation wird vor allem auf die Rolle der Kultur und der Übersetzung von Kulturbildern / Selbstbildern / Weltbildern eingegangen.
Identity Construction and Cultural Variety in Günter Grass and Marcel Reich-Ranicki’s Autobiographies as a Translation Challenge
Identitätskonstruktion und Kulturvielfalt der Autobiographien von Günter Grass und Marcel Reich-Ranicki als translatorische Herausforderung
Wydział Neofilologii: Instytut Filologii Germańskiej
Keywords: przekład literacki; literary translation; Literarische Übersetzung; krytyka przekładu literackiego; translation critique; Übersetzungskritik; autobiografia; autobiography; Autobiographie; konstrukcje tożsamości; identity construction; identity construction; Identitätskonstruktion